Quality of life of the patients with rheumatoid arthritis – preliminary results - Moćko, Justyna; Zurzycka, Patrycja (Nursing in the 21st Century, 2013)
QUALITY OF LIFE OF THE PATIENTS WITH RHEUMATOID ARTHRITIS – PRELIMINARY RESULTS Aim. The aim of the study was the assessment of quality of life in psychological, physical, environmental correlation and social relationships sphere, and also determining the influence of the results on the subjective assessment of quality of life of patients with rheumatoid arthritis. Material and methods. The study included a group of 55 patients with rheumatoid arthritis. The quality of life was tested with WHOQOL-BREF and HAQ questionnaires. To measure the pain intensity, the visual analogue scale in descriptive and numerical version was used. Results: In the tested group, there was observed a statistically relevant dependence between WHOQOL-BREF questionnaire results and social support in the environmental domain (r=0.298), number of children (r=0.279) and the level of education (r=0.279) in social sphere and frequency of pain occurrence in physical (r= -0.322) and social (r= -0.285) sphere. Conclusions. Socio-demographical elements that determine the quality of life of the patients with rheumatoid arthritis include: social support, level of education and number of children. Clinical elements include the frequency of pain occurrence.